Ten technologies to save the planet : energy options for a low-carbon future - Goodall, Chris (Greystone Books, 2010)
We face the dual crises of peak oil and climate change. How will we meet future global energy demands? Goodall combines cutting-edge analysis and fascinating stories of the inventors, scientists, and entrepreneurs developing real-world technologies.